Método didáctico ecológico activo influyente en, el aprendizaje significativo del Área curricular de Ciencia y Ambiente en Educación Primaria - Mendoza Chávez, Wilmer Francisco (2002)
The present experimental investigation was carried out with students of the sixth grade of primary education of the Educational Center number zero, zero five five one, located in the District of Yorongos, county of Rioja, Region of San Martin. The problem, general objective and hypothesis have been structured by means of the relationship of the variable Active Ecological didactic method and their influence in the significant learning. The theoretical body of the Active Ecological didactic method has been systematized, endowing him of a purpose, of an action field, of a structure composed by four stages: conceptual discovery, experimentation, concrete educational project, each stage with similar processes (planning, obtaining of information, development and plenary); of a theoretical support based on the principies of the active methodology, in the foundations epistemológicos and psicopedagist, constructivistas and finally of the biology of the learning. The influence with statistical significatividad of the Active Ecological didactic method in the significant learning, it has been the acceptance of the alternating hypothesis. The universe conformed by the students of the sixth grade, it has been studied in an effected at random; twenty integrated the experimental group and twenty the group control. The investigation hypothesis finds consistency in the confrontation of the results since these they are consequences of the theories that sustain to the method. In that logic the inferred conclusions sustain that by means of the Active Ecological didactic method, the students builds and they reconstruct the knowledge, they solve problems, it is developed with freedom, he/she learns inter and intro personal and they stimulate the neurons of their two cerebral hemispheres. The parameter statistical employee in the hypothesis test has been to normal distribution (z).